(untitled) (Tempo e Argumento, 2009)
The largest enhancements of history come from the dignification conquered by the historical memory, whether that of women, regional minorities, religious minorities or social groups without a voice. This journey into the collective memory of the most diverse social experiences, enriched the history constantly in his historiographical and reflexive stage. Paul Ricoeur shows how memory is the first matrix of history and is the basis for the recovery of history. This interpenetration it to generate tensions, sometimes strong, but this is the inescapable horizon of relations history/memory.